A qualitative assessment of body image in adolescents and young adults (AYAs) with cancer. Issue 4 (19th December 2020) - Moore, Justin B.; Canzona, Mollie R.; Puccinelli‐Ortega, Nicole; Little‐Greene, Denisha; Duckworth, Katie E.; Fingeret, Michelle C.; Ip, Edward H.; Sanford, Stacy D.; Salsman, John M.
Abstract: Context: Among adolescents and young adults (AYAs), cancer and its treatment can disturb body image in distinct ways compared to younger or older individuals. Objective: Since AYA body image is not well understood, this study was designed to develop a conceptual framework for body image in AYAs with cancer. Methods: Concept elicitation interviews were conducted with 36 AYA patients [10 adolescents (15–17 years), 12 emerging adults (18–25 years), 14 young adults (26–39 years)] and health care providers ( n  = 36). The constant comparative method was used to analyze for themes and properties, with themes considered saturated if they were present and salient across participant sets. Results: Twenty themes emerged from participant data. Three themes illustrate a shared understanding of patients' experience of body image: (1) physical changes produce shifts in identity and experience of self; (2) precancer body image shapes how the AYA experiences cancer‐related physical changes, and (3) changes to the body are upsetting. Nine themes were unique to patients while eight themes were unique to providers. Patient body image experiences were found to evolve over time, largely affected by concerns about how others view them. Providers appeared attuned to AYA patient body image but recognized that it is not systematically addressed with patients. Conclusion: More striking than differences between patient groups is the consistency of themes that emerged. The conceptual framework of body image developed from these data offers an important step toward addressing body image concerns for AYA patients.